BRIBERY AND GRATUITY: REGULATORY ANALYSIS AND JUDICIAL RESPONSE - Ach. Tahir; Mahrus Ali; Muhammad Arif Setiawan (Jurnal Ius Constituendum, 2021)
This paper is aimed at analyzing the concepts and parameters to determine an act as a bribery and gratuity in the Anti-Corruption Law and court cases.  This involved the application of the doctrinal legal research to understand these differences. The results of this study showed that bribery requires a meeting of mind between the bribe givers and bribe recipients which is not found in gratuity. The reporting mechanism and the reversal burden of proof do not apply to bribery while Operation Catching Hand does not apply to gratuity due to its inability to satisfy the provisions of the Criminal Procedure Code. Criminal sanctions are also imposed on both the giver and the recipient of a bribe while the act of a giver in gratuity is not considered as a criminal offense. The study also found that the court failed to apply these essential differences.